2023
DOI: 10.1002/yea.3836
|View full text |Cite
|
Sign up to set email alerts
|

The arginine transporter Can1 acts as a transceptor for regulation of proline utilization in the yeast Saccharomyces cerevisiae

Abstract: Proline is the most abundant amino acid in wine and beer, because the yeast Saccharomyces cerevisiae hardly assimilates proline during fermentation processes. Our previous studies showed that arginine induces endocytosis of the proline transporter Put4, resulting in inhibition of proline utilization. We here report a possible role of arginine sensing in the inhibition of proline utilization. We first found that two basic amino acids, ornithine, and lysine, inhibit proline utilization by inducing Put4 endocytos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…PKA signaling is mainly activated by the dissociation of the catalytic (Tpk1, 2, 3) and regulatory (Bcy1) subunits of PKA, which is caused by a rapid increase in intracellular cAMP levels. We also reported that basic amino acids such as arginine rapidly activate PKA activity without increasing cAMP levels [22]. The arginine transporter Can1 mediates the activation of PKA using basic amino acids.…”
Section: Resultsmentioning
confidence: 90%
“…PKA signaling is mainly activated by the dissociation of the catalytic (Tpk1, 2, 3) and regulatory (Bcy1) subunits of PKA, which is caused by a rapid increase in intracellular cAMP levels. We also reported that basic amino acids such as arginine rapidly activate PKA activity without increasing cAMP levels [22]. The arginine transporter Can1 mediates the activation of PKA using basic amino acids.…”
Section: Resultsmentioning
confidence: 90%
“…ScCAN1 deletion enhances tolerance to canavanine, a toxic arginine analog (Suizu et al, 1989). Interestingly, some researchers have shown that ScCan1 has other functions besides arginine uptake; e.g., regulation of intracellular stress systems, longevity, biofilm formation, and endocytosis (Beaupere et al, 2017;Gournas et al, 2018;Nishimura et al, 2022;Tanahashi et al, 2022). Here, we identified the arginine transporter Can1of C. glabrata (named CgCan1).…”
Section: Textmentioning
confidence: 94%
“…In general, S. cerevisiae cells take up arginine mainly through Can1 but partially through Alp1 and Gap1 (Zhang et al, 2016). One of four plasmids, i.e., pRS416-PADH1-yEGFP-TCYC1 (+GFP), pRS416-PADH1-ScCAN1-yEGFP-TCYC1 (+ScCan1-GFP), pRS416-PADH1-CAGL0J08162g-yEGFP-TCYC1 (+CAGL0J08162g-GFP), or pRS416-PADH1-CAGL0J08184g-yEGFP-TCYC1 (+CAGL0J08184g-GFP), was introduced into S. cerevisiae gap1Δalp1Δcan1Δ cells, which lack arginine transport activity (Tanahashi et al, 2022). On a medium with ammonium as the sole nitrogen source (SD medium; +NH4 + ), there was no significant difference in growth among all strains (Fig.…”
Section: Textmentioning
confidence: 99%
“…Three growth media were used in this study: a synthetic complete medium (SC) (2% glucose, 0.67% yeast nitrogen base without amino (Nishimura et al, 2022;Tanahashi et al, 2023;Nishimura et al, 2023b). Strain alp1Δ was constructed from WT by integrating the kanMX4 gene cassette amplified by PCR with gene-specific primer sets (ALP1 deletion Fw and Rv, listed in Supplementary Table S2) and pFA6a-kanMX4 (purchased from the AddGene repository).…”
Section: Culture Media Strains Plasmidsmentioning
confidence: 99%